Co-sputtered Cu2ZnTi(S:Se)4 absorbers for thin film solar cells. (January 2020) - Batibay, Derya; Ocak, Yusuf Selim; Genisel, Mustafa Fatih; Turan, Rasit
Abstract: Thin film solar cells are an exciting topic for low cost and high efficient solar cells. Owing to the high price of the indium metal in the fabrication of copper indium gallium diselenide (CIGS) solar cells, Cu2 ZnSn(SSe)4 thin films are used as a new material to reduce the cost and increase the efficiency. As an alternative absorber material for solar cell production, Cu2 ZnTi(S:Se)4 thin films were deposited by the co-sputtering method at various temperatures. During the deposition, Cu, ZnSe and Ti targets were used as metal sources. The Cu2 ZnTi(S:Se)4 thin films were annealed in H2 S:Ar (1:9) atmosphere. The morphological, structural and optical properties of Cu2 ZnTi(S:Se)4 thin films was analyzed using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD) Raman spectroscopy and UV–Vis–NIR spectrometer. It was seen that the thin films had good optical absorption till the infrared region and the band gap of the Cu2 ZnTi(S:Se)4 thin films were smaller than the conventional Cu2 ZnSnS4 thin films. Furthermore, fabrication of a solar cell with 1.96% power conversion efficiency was reported using a Cu2 ZnTi(S:Se)4 thin film as a low cost absorber layer. Highlights: Cu2 ZnTi(S:Se)4 thin films were deposited by the co-sputtering method. The films were annealed at 550 °C in H2 S:Ar atmosphere. Morphological, structural, and optical properties were determined. A solar cell with 1.96% efficiency was fabricated.